(untitled) (CIPEEX, 2025)
Systemic arterial hypertension (SAH) is considered one of the most prevalent non-communicable chronic diseases (NCDs) worldwide. This condition presents modifiable risk factors—such as inadequate sleep, smoking, alcohol consumption, and sedentary behavior—which may be associated with the exhaustive routine of medical students. This study investigated the relationship between NCD risk factors among medical students at UniEVANGÉLICA and elevated blood pressure (BP), as well as the potential development of SAH. Data were collected via a structured questionnaire and blood pressure measurement. Analyses revealed that smoking was the risk factor most associated with increased systolic (SBP) and diastolic blood pressure (DBP), and there was a relative increase in mean DBP among sedentary students and those who sleep five hours or less per day. Alcohol consumption showed no significant variation in SBP or DBP compared to the overall mean; however, it was a common habit among 72.8% of the sample.